Cinnamon and ginger extracts attenuate diabetes-induced inflammatory testicular injury in rats and modulating SIRT1 expression - Ghadeer I. Alrefaei; Hailah M. Almohaimeed; Sami A. Algaidi; Mohammed Saad Almuhayawi; Fatma Mohamed AbdAllah; Nouf S. Al-Abbas; Nehad A. Shaer; Zuhair M. Mohammedsaleh; Fayez M Saleh; Nasra Ayuob (Journal of Men's Health, 2023)
The current study aimed to evaluate the efficacy of simultaneous administration of Zingiber officinale (ginger) and Cinnamomum cassia (cinnamon) extracts in mitigating testicular changes associated with diabetes mellitus in rats and to investigate its molecular mode of action. After induction of diabetes using streptozotocin, 36 male rats were divided to six groups namely control, diabetic, metformin-treated, cinnamon-treated, ginger-treated and combined, each group having 6 rats. Fasting blood glucose, serum insulin, testosterone was measured. Expression of inflammatory mediators; tumor necrosis factor-alpha (TNF-α), Nuclear factor kappa B (NF-κB) and Sirtuin 1 (SIRT1) was assessed in the testicular tissue. Histopathological changes in the testis were observed and spermatogenesis and apoptosis were assessed immunohistochemically. The histological and biochemical studies of the untreated group confirmed structural changes in testes induced by diabetes. Oral administration of ginger and cinnamon increased insulin level significantly increased while the blood glucose level significantly decreased in diabetic rats, improving structural testicular changes considerably. Joint intake of ginger and cinnamon increased antihyperglycemic, antioxidant and anti-inflammatory effects markedly improving the testicular injury compared to the administration of either of them. SIRT1 expression in the testis significantly increased in ginger plus cinnamon-treated rats. These results indicate that when administrated together, ginger and cinnamon synergistically enhanced antioxidant, antiapoptotic and anti-inflammatory effects and induced antihyperglycemic effect comparable to metformin. The combination of ginger and cinnamon also upregulated SIRT1 in the testis.